Democratic epistemics: an experiment on how to improve forensic science - Roger G. Koppl (Max Planck Institute of Economics, 2006)
In "monopoly epistemics”, one privileged actor is asked to identify the truth. In “democratic epistemics”, several independent parties are asked. In an experiment contrasting them, democratic epistemics reduced the systemic error rate by two-thirds, supporting the claim that replacing monopoly epistemics with democratic epistemics would reduce error rates in forensic science and other areas. It also suggests first, the potential of “epistemic systems design”, which employs the techniques of economic systems design to address issues of veracity, rather than efficiency, and second, the value of “experimental epistemology”, which employs experimental techniques in the study of science. Research of the sort described here puts evolutionary epistemology into practice by seeking to find the proper design principles for error-correcting social institutions.
Keywords: 330